SISTEM INOVASI DAERAH KOTA PEKALONGAN - Mahirun Mahirun (LPPM Universitas Pekalongan, 2014)
Strengthening regional innovation systems (sida) is one of the government policies that is based on joint regulations of the state minister for research and technology and the minister of home affairs concerning strengthening of regional innovation systems (sida). The aim of the pekalongan city development innovation analysis study is to produce data/information in terms of products, goods and services found in the pekalongan city area, especially in the district of west pekalongan to be used as material in the development of the pekalongan city regional innovation system. Data analysis techniques in this study used the steps: 1) data reduction, 2) data display, and 3) conclusion drawing / verification. the survey target objects according to the existing sector, namely the industrial sector, the trade sector, and the cooperative sector that has the value of innovation both goods and services. The results of the study found that products that have high innovation value proved to be very popular with consumers, for example are; wooden toys used